Redefining Educational Leadership in the Sultanate of Oman: From Standardization to Empowerment within a Paradigm Shift - Aljaradi, Saif Hamad Khamis; Marzooghi, Rahmatoallh; Torkzadeh, Jafar; Heydari, Elham (Journal of Educational and Psychological Sciences, 2025)
This article aims to reconstruct the concept of educational leadership in the Sultanate of Oman through a critical hermeneutic approach, grounded in the paradigm shift from traditional leadership models to a more transformative and innovative framework. The study employs a theoretical-analytical method, interrogating the prevailing assumptions of dominant educational leadership discourses in light of global sociocultural and technological transformations that demand more human-centered, adaptive, and creative models. The paper deconstructs the institutional and cultural constraints of traditional leadership and identifies seven key dimensions that constitute structural challenges to transformational change: excessive centralization, weak delegation, absence of critical formation, the gap between discourse and practice, entrenched bureaucratic culture, reliance on quantitative evaluation models, and conceptual voids in official policy documents. In response, the article proposes an alternative transformative model based on participatory, hermeneutic, and ethical foundations. It calls for empowering schools internally and redefining the role of educational leaders as thinkers, designers, and cultural agents—rather than mere administrative executors. The study recommends redesigning leadership development frameworks in Oman, liberating educational policies from rigid normative models, and fostering a culture of institutional innovation through reflective leadership capable of generating meaning, not just complying with directives.